Poor sleep quality among patients with Parkinson’s disease: a meta-analysis and systematic review - Si, Tong Leong; Wang, Yue-Ying; Li, Jia-Xin; Bai, Wei; Sun, He-Li; Rao, Shu-Ying; Zhu, Han-Yu; Ungvari, Gabor S.; Su, Zhaohui; Cheung, Teris; Ng, Chee H.; Xiang, Yu-Tao; et al. (Frontiers in Psychiatry, 2025)
ObjectivePoor sleep quality is common among patients with Parkinson’s disease (PD), although the reported prevalence rates vary between studies. This meta-analysis examined the overall prevalence of poor sleep quality in patients with PD and identified potential factors contributing to the differences in prevalence across studies.MethodsBoth PRISMA and MOOSE guidelines were applied in this meta-analysis. A systematic search was conducted in PubMed, EMBASE, PsycINFO, Web of Science, CNKI and Wangfang from their inception to November 4, 2023. Studies were selected based on predefined PICOS criteria (i.e., PD patients, prevalence of poor sleep quality, cross-sectional/cohort designs). Study quality/risk of bias was assessed using a standardized 8-item tool. Pooled prevalence was calculated sources of heterogeneity (e.g., age, sex, depression, anxiety, cognition scores, disease severity, and medication dose) were explored via subgroup and meta-regression analyses. A random-effects model was utilized to calculate the overall prevalence and corresponding 95% confidence intervals (CIs).ResultsIn total, 63 studies involving 9,382 PD patients were included. The overall prevalence of poor sleep quality was 58.07% (95% CI: 54.26–61.88%). Higher rates were related to various factors including studies from Europe & Central Asia, Upper middle income countries, mixed patient sources, lower diagnostic cutoffs, and use of Movement Disorder Society PD criteria. Meta-regression analysis showed that late onset PD was associated with poorer sleep quality in patients with PD.ConclusionPoor sleep quality is common in PD patients. Regular monitoring of sleep quality and promotion of sleep hygiene should be prioritized in the management of patients with PD. Additionally, further research on sleep and PD is warranted in low- and middle-income countries to ensure the applicability of findings across diverse populations.Systematic Review Registrationhttps://inplasy.com/inplasy-2023-10-0022/, identifier INPLASY2023100022.